Jumpstart 2000—The Maine Economic Improvement Strategy: A Targeted Investment in Research and Development - Lawrence, Mark; Jacobson, George (Maine Policy Review, 1997)
In recent years Maine has ranked 50th in per capita spending on university-based research and development in the United States, a distinction that an increasing number of Maine policymakers, citizens, business representatives and researchers find alarming. Citing the positive gains R&D investments have shown in other states, not the least of which is improved economic performance, the authors set forth an argument for investing in Maine’s public R&D infrastructure. Whether and how to make such investments have been the subjects of recent debate in many states.